Transformasi Pembelajaran melalui Manajemen Inovasi - Puspito Rini, Puput (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Learning transformation is the most important agenda of global education reform that includes systematic efforts to change the way knowledge is delivered and internalized, from designing responsive curricula to building institutional ecosystems that support sustainable innovation. This study aims to examine the transformation of learning through innovation management in four dimensions, namely innovation management strategies to improve the quality of learning, the role of digital technology, the contribution of organizational learning and institutional innovation culture, as well as the contextual-cultural dimension in the implementation of learning innovation. The